2017
DOI: 10.1007/s11934-017-0729-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urethral Stricture and Bladder Neck Contracture Following Primary and Salvage Treatment of Prostate Cancer

Abstract: Rates of stenosis after prostate cancer treatment appear similar across all primary treatment modalities including radical prostatectomy, radiation therapy, cryoablation, and high-intensity focused ultrasound in contemporary series. Urethral dilation and urethrotomy continue to report moderate patency rates. Urethroplasty achieves high patency rates even for long strictures, but more extensive reconstruction increases the risk of postoperative urinary incontinence. Recent AUA guidelines on urethral strictures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 70 publications
0
29
0
3
Order By: Relevance
“…3). For MIBC, radical cystectomy is often performed, followed by chemotherapy and radiotherapy, but only 50% of patients will survive for 5 years (3,4). Thus, there is still a need for finding new methods for the treatment of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3). For MIBC, radical cystectomy is often performed, followed by chemotherapy and radiotherapy, but only 50% of patients will survive for 5 years (3,4). Thus, there is still a need for finding new methods for the treatment of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] For patients with muscle invasive BC, radical cystectomy and TURBT followed by concurrent radiation therapy and systemic chemotherapy (trimodality therapy) are recommended, while the trimodality therapy has the shortcoming of large injure, resulting in poor quality of life and 5 year survival rate of BC patients. [ 6 , 7 ] Thus, it is necessary to develop novel management options for patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Sacco et al [26] showed a 2.4-fold higher RR of remaining incontinent after RRP, if the patient developed stenosis. It is likely that management of stenosis by transurethral incision leads to a higher risk of long-term complications, with postrepair urinary incontinence being the most severe complication [27]. Another mechanism could be the negative influence of scar tissue on the external sphincter and its function in continence control.…”
Section: Discussionmentioning
confidence: 99%